The composition of gluten proteins and their effect on the rheological properties of gluten - Uri, Csilla; Tóth, Árpád; Sipos, Péter; Borbélyné Varga, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2006)
Wheat is the major cereal component of bread in the world and is grown worldwide. Of the cereals only the bread wheats – and less the triticale – includes storage proteins that play an important role in the performance of gluten. Proteins of gluten complex may be present in two classes: − low molecular weight (gliadin-) components, and − high molecular weight (glutenin-) components. Gliadins shown appreciable heterogenity and can be separated into 40-50 components with gel electrophoresis. The composition of gliadins is employable for the identification the wheat varieties and to investigate the varieties. In the decreasing electrophoretic mobility sequence may be distinguish α-, β-, γ- and ω-gliadins. A glutenin subunits may be include in two classes: − high molecular weight glutenin subunits (HMW-GS), − low molecular weight glutenin subunits (LMW-GS). Wheat varieties can be identified by glutenin and their quality selection is also possible. The gliadin’s polypeptides encoding genes are located on the short arm of chromosomes 1A, 1B and 1D, 6A, 6B and 6D. Genetic coding for HMW subunits is located on the long arms of chromosomes 1A, 1B and 1D, the LMW-GS are also located on chromosomes 1A, 1B and 1D (Glu-3 loci) near the gliadin-coding loci. Storage proteins affect the rheological properties of gluten by two factors: 1. The quality and quantity of the protein components of the gluten complex, 2. The interactions between the protein fractions.